Tofersen decreases neurofilament levels supporting the pathogenesis of the SOD1 p.D91A variant in amyotrophic lateral sclerosis patients - Weishaupt, Jochen H.; Körtvélyessy, Péter; Schumann, Peggy; Valkadinov, Ivan; Weyen, Ute; Hesebeck-Brinckmann, Jasper; Weishaupt, Kanchi; Endres, Matthias; Andersen, Peter M.; Regensburger, Martin; Dreger, Marie; Koch, Jan C.; et al. (Communications Medicine, 2024)
Background: Since the antisense oligonucleotide tofersen has recently become available for the treatment of amyotrophic lateral sclerosis (ALS) caused by mutations in SOD1, determining the causality of the over 230 SOD1 variants has become even more important. The most common SOD1 variant worldwide is p.D91A (c.272A > C), whose causality for ALS is contested when in a heterozygous state. The reason is the high allele frequency of SOD1D91A in Europe, exceeding 1% in Finno-Scandinavia. Methods: We present the clinical disease course and serum neurofilament light chain (NfL) results of treating 11 patients either homo- or heterozygous for the SOD1D91A allele for up to 16 months with tofersen. Results: Tofersen decreases serum neurofilament levels (sNFL), which are associated with the ALS progression rate, in the 6 ALS patients homozygous for SOD1D91A. We observe significantly lower sNfL levels in the 5 patients heterozygous for SOD1D91A. The results indicate that both mono- and bi-allelic SOD1D91A are causally relevant targets, with a possibly reduced effect size of SOD1D91Ahet. Conclusions: The finding is relevant for decision making regarding tofersen treatment, patient counseling and inclusion of SOD1D91A patients in drug trials. As far as we are aware, the approach is conceptually new since it provides evidence for the causality of an ALS variant based on a biomarker response to gene-specific treatment.
CRIS-Team Scopus Importer:2024-09-20